Photochemistry - Photophysics of fluorescently labeled oligomers and polymers - Catherine De Castro (Royal Society of Chemistry, 2013)
Fluorescently labeled oligomers and polymers are nowadays of extreme relevance in the characterization of polymer dynamics, protein folding, as molecular rulers, chemosensors, etc. This contribution makes a revision of the photophysical characteristics of probes able to form excited dimers (excimers) in particular of pyrene labeled oligomers or polymers. The presence of different dimer conformations in the ground and excited states, the steric hindrance in particular with relation to the connection of pyrene through positions 1 or 2 leading to the formation of one or two excimers, etc., are discussed. The models used to investigate the kinetics of excimer formation, with the appropriate equations, are described (including the rate constants for a relevant number of published data in different systems). Particular emphasis is put on the properties of these probes in the colloidal domain and as chemosensors.